2018
DOI: 10.1002/jccs.201700397
|View full text |Cite
|
Sign up to set email alerts
|

An electromembrane extraction–HPLC‐UV analysis for the determination of valproic acid in human plasma

Abstract: In this study, an electromembrane extraction (EME) method combined with a simple HPLC-UV analysis was developed and validated for the determination of valproic acid in human plasma samples. The major parameters influencing EME procedure, namely the solvent composition, voltage, pH of acceptor and donor solutions, salt effect, and time of extraction, were evaluated and optimized. The drug was extracted from the donor aqueous sample solution (pH 5) to the acceptor aqueous solution (pH 13). The donor and acceptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Ghani et al 96 reported a HPLC-UV method for determination of diclofenac in urine and plasma samples after its microextraction by a Mg-Al-layered double hydroxide (LDH)-GO mixed-matrix membrane. Similar works were performed for determination of L-cysteine in spiked plasma and urine samples after extraction by using zinc organic polymer (Zn-MOP) as a sorbent, 97 for simultaneous determination of losartan and valsartan in spiked plasma samples after extraction with stir bar sorptive extraction (SBSE) based on acrylate monolithic polymer, 98 for determination of vincristine in spiked plasma and urine samples by using a solvent bar microextraction (SBME) with water at pH 10.7 as donor phase, 1-octanol as the supported liquid membrane and an aqueous receiving phase (pH =3.1), 99 for simultaneous determination of oxazepam, flurazepam, and diazepam in hair, nail and blood samples after extraction by using a vortex assisted dispersive solid phase extraction approach based on crab shell powder as micro-sorbent, 100 for determination of rizatriptan in spiked plasma and urine samples after extraction by using SBME technique, 101 for determination of diclofenac, ibuprofen, and mefenamic acid in spiked plasma and urine samples after extraction with centrifugeless ultrasoundassisted dispersive micro solid-phase extraction with Zn-Al-LDH-MWCNT nanohybrid as a nanosorbent coupled with salting-out ultrasound-assisted liquid-liquid microextraction based on solidification of a floating organic droplet, 102 for determination of zolpidem in spiked plasma and serum samples after an EME procedure, 103 for determination of phenazopyridine after a extraction procedure by coupling EME and packing a sorbent (a cation exchanger) with reported value of 33 µg L -1 and 237.3 µg L -1 for phenazopyridine in urine sample of patients treated with it respectively after 9 and 12 hour, 104 for determination of diclofenac in spiked plasma and urine samples after extraction by HF-LPME, 105 for determination of valproic acid in spiked plasma samples after extraction by using HF-EME method, 106 and for determination of exemestane, letrozole and paclitaxel in spiked urine samples after extraction by using three-phase HF-LPME based on two immiscible organic solvents (acetonitrile and n-dodecane). 107 Magnetic solid phase extraction (MSPE) as an alternative method for SPE have mostly been used for sample preparation before HPLC-UV.…”
Section: High-performance Liquid Chromatography (Hplc)-uv Detectormentioning
confidence: 90%
“…Ghani et al 96 reported a HPLC-UV method for determination of diclofenac in urine and plasma samples after its microextraction by a Mg-Al-layered double hydroxide (LDH)-GO mixed-matrix membrane. Similar works were performed for determination of L-cysteine in spiked plasma and urine samples after extraction by using zinc organic polymer (Zn-MOP) as a sorbent, 97 for simultaneous determination of losartan and valsartan in spiked plasma samples after extraction with stir bar sorptive extraction (SBSE) based on acrylate monolithic polymer, 98 for determination of vincristine in spiked plasma and urine samples by using a solvent bar microextraction (SBME) with water at pH 10.7 as donor phase, 1-octanol as the supported liquid membrane and an aqueous receiving phase (pH =3.1), 99 for simultaneous determination of oxazepam, flurazepam, and diazepam in hair, nail and blood samples after extraction by using a vortex assisted dispersive solid phase extraction approach based on crab shell powder as micro-sorbent, 100 for determination of rizatriptan in spiked plasma and urine samples after extraction by using SBME technique, 101 for determination of diclofenac, ibuprofen, and mefenamic acid in spiked plasma and urine samples after extraction with centrifugeless ultrasoundassisted dispersive micro solid-phase extraction with Zn-Al-LDH-MWCNT nanohybrid as a nanosorbent coupled with salting-out ultrasound-assisted liquid-liquid microextraction based on solidification of a floating organic droplet, 102 for determination of zolpidem in spiked plasma and serum samples after an EME procedure, 103 for determination of phenazopyridine after a extraction procedure by coupling EME and packing a sorbent (a cation exchanger) with reported value of 33 µg L -1 and 237.3 µg L -1 for phenazopyridine in urine sample of patients treated with it respectively after 9 and 12 hour, 104 for determination of diclofenac in spiked plasma and urine samples after extraction by HF-LPME, 105 for determination of valproic acid in spiked plasma samples after extraction by using HF-EME method, 106 and for determination of exemestane, letrozole and paclitaxel in spiked urine samples after extraction by using three-phase HF-LPME based on two immiscible organic solvents (acetonitrile and n-dodecane). 107 Magnetic solid phase extraction (MSPE) as an alternative method for SPE have mostly been used for sample preparation before HPLC-UV.…”
Section: High-performance Liquid Chromatography (Hplc)-uv Detectormentioning
confidence: 90%
“…They are useful in monitoring the therapeutic concentration of a substance, treatment progress, and side effects. Several methods for determination of valproic acid are known, namely: thin layer chromatography [5], liquid chromatography [6][7][8][9], high performance liquid chromatography [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], ultra high performance liquid chromatography [4,25,26], ultra performance liquid chromatography [27][28][29][30][31], gas chromatography [4,18,[32][33][34][35][36][37][38], capillary electrophoresis [39,40], voltamperometry [41], valproateselective electrode [42], and colorimetry [43].…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of valproic acid was determined in biological samples [4][5][6][7][8][9][10][11][12][13]16,[19][20][21][22][24][25][26][27][28][29][30][31][32][33][34][35][36][38][39][40]. Only a few studies report the determination of valproic acid in pharmaceutical preparations [14,17,20,23,35,37,41,42].…”
Section: Introductionmentioning
confidence: 99%
“…It is a well known anticonvulsant drug which nowadays is widely examined for new therapeutic indications [ 13 ]. Analytical methods, such as HPLC [ 14 , 15 , 16 , 17 , 18 ], LC-MS/MS [ 19 , 20 , 21 , 22 , 23 ], gas chromatography (GC) [ 24 , 25 , 26 ] and gas chromatography–mass spectrometry (GC-MS) [ 27 ] were reported for the determination of VPA in biological matrices. Most of the previously reported HPLC and GC methods required complex sample pretreatment or detection, e.g., multistep derivatization for UV detection [ 14 , 17 ], multistep derivatization for fluorimetric detection [ 15 , 16 ], or complex extraction [ 18 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%